An approach to reduce Descemet's membrane scrolling: Relevance to Descemet's membrane endothelial keratoplasty (DMEK) - Harminder S Dua; Rui Freitas; Youssef Sadek; Darren S J Ting; Mario Nubile; Imran Mohammed; Dalia G Said (Indian Journal of Ophthalmology, 2023)
Purpose: We aimed to determine whether Descemet's membrane (DM) scrolling occurs primarily along the vertical or horizontal axis and establish whether oval trephination along the axis of least scrolling can reduce the grade of the scroll. Methods: The longest limbus-to-limbus axis on 28 sclerocorneal discs was taken as the horizontal axis. The horizontal (n = 7) or (right angles to it) vertical (n = 6) axis was marked on DM before peeling it off. The direction and grade of scrolling was observed. Narrow strips (3–4 mm wide) were then cut along the two axes (n = 4 each) and the scrolling pattern was observed. Ellipses (7 × 9 mm) of DM were punched along the two axes (n = 6 each) and the scrolls graded. Immunofluorescent staining for elastin on horizontal and vertical tissue sections from three DM samples was performed. The intensity and thickness of elastin staining were measured. Results: Twenty-four (85.72%) DM samples showed scrolling along the horizontal axis, none showed scrolling along the vertical axis, and four (14.28%) samples showed a spiral scroll, regardless of which axis was marked (grade 3.7 and 3.6). Vertically oval discs showed significantly reduced scrolling (grade 1.2) compared to horizontally oval discs (grade 3.5). Narrow strips of DM showed a similar scrolling pattern. Immunohistology showed no difference in any of the parameters examined along the two axes or from the center to the periphery. Conclusion: DM scrolls primarily along the horizontal axis. Vertically oval DM samples show minimal scrolling, which can be an advantage in DMEK. Differential scrolling is not determined by the distribution of elastin.